Role of hypothalamus nociceptin/orphanin FQ in pre-ovulatory luteinizing hormone surge of estrogen and progesterone-primed, ovariectomized rats - An Xiao-fei; Yu Jiang-yi; Chen Bo-ying; Zhang Su-lin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the role of hypothalamus nociceptin/orphanin FQ (OFQ) and its endogenous receptor, the opioid receptor-like 1 receptor (ORL1 receptor) in the estrus cycle of female rats. Method: Radioimmunoassay was used to detect the effect of the intracerebroventricular (icv) administration of OFQ and/or the ORL1 receptor antagonist [Nphe1]Nociceptin(1-13)NH2, that is, NC13 on luteinizing hormone (LH) levels of estrogen- and progesterone (EBP)-primed, ovariectomized (OVX) rats (EBP-primed OVX rats). RT-PCR, Western blotting, and immunohistochemistry techniques were adopted to observe the changes of OFQ and the ORL1 receptor in the pre-optic area (POA) and the medial basal hypothalamus (MBH) of the estrus cycle of female rat. Results: Pre-ovulatory LH surges in EBP-primed, OVX rats were significantly reduced by icv administration of 20 and 200 nmol OFQ (P